Effect of a physical therapeutic intervention on locomotive syndrome in the elderly patients with Parkinson's disease and sarcopenia - Ivanna V. Didoha; Mariia G. Aravitska; Yaroslav M. Yatsiv; Oleh V. Hrecheskyi (H.S. Skovoroda Kharkiv National Pedagogical University, 2023)
Purpose: to evaluate the effectiveness of the effect of physical therapy on the indicators and severity of locomotive syndrome in elderly patients with Parkinson's disease and sarcopenia. Material and methods: 57 elderly people with Parkinson's disease in combination with sarcopenia were examined. They were divided into two groups: group 1 (followed the principles of standard protocols of outpatient rehabilitation) and group 2 (followed the physical therapy program, which was developed in terms of patient-centered model of rehabilitation taking into account the specifics of each comorbid condition with the use of functional training on the «Prosedos» platform, therapeutic exercises, massage, occupational therapy, nutrition correction, and patient education). The control group consisted of 24 elderly people without signs of sarcopenia and Parkinson's disease. The effectiveness of the program was evaluated by the dynamics of 25-question Geriatric Locomotive Function Scale, Dynamic Gait Index, Functional Gait Assessment, Activities Balance Confidence Scale, Modified Parkinson Activity Scale. Results: Elderly patients with Parkinson's disease and sarcopenia were diagnosed with locomotive syndrome stage 2 (according to the 25-question Geriatric Locomotive Function Scale), which manifested itself as a high risk of falling and deteriorating dynamic balance (according to Dynamic Gait Index, Functional Gait Assessment), decreased confidence in maintaining balance during activities (according to Activities Balance Confidence Scale), violation of activities of daily living (according to Modified Parkinson Activity Scale); it was statistically significantly worse than in their peers (p<0.05). The developed program of physical therapy led to a statistically significant (p<0.05) improvement of all studied parameters of locomotive syndrome in comparison with baseline and the condition of patients who received standard restorative correction. Conclusions: Elderly patients with comorbid pathology (Parkinson's disease and sarcopenia) need new physical therapy programs considering the specifics of each disease and its correcting, the presence of locomotive syndrome to improve social and domestic activity of patients and reduce health risks associated with geriatric syndromes - falls and frailty.